Gas turbine handbook [ principles and practice - Giampaolo, Tony , 1939- (Lilburn, GA.Fairmont Press;Boca Raton, FL : CRC Press, 2009)
"Newly revised and edited, this reference provides the fundamental information you'll need to understand both the operation and proper application of all types of gas turbines. The full spectrum of hardware, as well as typical application scenarios are fully explored, along with operating parameters, controls, inlet and exhaust treatments, inspection, troubleshooting, noise control, inlet cooling for power augmentation and NOx control. A full chapter is devoted to microturbines. The fourth edition places additional emphasis on critical elements of centrifugal and axial compressors, including detailed information on the compression process and the parameters that impact it. The author has provided many helpful tips that will enable diagnosis of problems in their early stages and analysis of failures to prevent their recurrence."--BOOK JACKET
Description based on print version record
Includes bibliographical references and index
Keywords: Gas-turbines -- Handbooks, manuals, etc